Foundations of nursing practice themes, concepts, and frameworks - Hogston, Richard; Marjoram, Barbara A. (Basingstoke : Palgrave Macmillan, 2011)
Offering material relevant to the common foundation course, this book includes two new chapters on ethics in nursing and health informatics. It presents the contents organized into a theory/practice structure and also provides coverage of cultural and branch issues.
Previous ed.: 2007.
Includes bibliographical references and index.
Keywords: Nursing; Nursing -- Practice; Nursing Care; Nurse's Role